Pendidikan Seks Pada Anak Usia Dini Sebagai Upaya Menciptakan Tempat Wisata Aman Di Kelurahan Manggar Baru Kota Balikpapan - Nugroho, Bayu Aji; Uli Br. Purba, Theresia Dwi (ANDIL Mulawarman Journal of Community Engagement, 2024)
One of the efforts to prevent sexual abuse and violence in children is to provide sex education from an early age. Sexual harassment occurs because of a lack of sex education for children. By providing appropriate and age-appropriate sex education outreach, children can learn to recognize signs of inappropriate behavior and know how to report acts of sexual harassment to a trusted adult. The purpose of this community service activity is to build efforts to increase understanding, awareness, and provide information related to sexuality issues from an early age to students of SDN 010 Kelurahan Manggar Baru, so as to avoid sexual harassment and violence and create tourist attractions that have safe spaces for children -child. This work program activity is in the form of socializing "Early Age Sex Education" to students of SDN 010 Manggar Baru Village using the Service-Learning method. The results obtained were that the subjects were able to describe in illustrations what parts of the body that other people should not see and touch. The subject can also mention and demonstrate what to do when someone else wants to see and touch a part of the body that is not allowed to be touched by other people.